2021
DOI: 10.1080/21655979.2021.1975016
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of long non-coding RNA insulin-like growth factor 2-antisense suppressed hepatocellular carcinoma cell proliferation and metastasis by regulating the microRNA-520h/cyclin-dependent kinase inhibitor 1A signaling pathway

Abstract: 2021) Over-expression of long non-coding RNA insulin-like growth factor 2-antisense suppressed hepatocellular carcinoma cell proliferation and metastasis by regulating the microRNA-520h/ cyclin-dependent kinase inhibitor 1A signaling pathway, Bioengineered, 12:1, 6952-6966,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The profile of the cell cycle also changed, with the proportion of cells in G1 phase increasing by approximately 10%. miR-520h has a negative effect on HUVECs cell proliferation and other tumor cells including granulosa-like tumor cell (35,(42)(43)(44)(45). It was reported that miR-520h could target on IL-6R to inhibit cell growth (42).In the current study, an anti-proliferation property of miR-602 was revealed, we also identified that IL-6R was turned downed by miR-602 and induced by S-3′UTR.…”
Section: Discussionsupporting
confidence: 54%
“…The profile of the cell cycle also changed, with the proportion of cells in G1 phase increasing by approximately 10%. miR-520h has a negative effect on HUVECs cell proliferation and other tumor cells including granulosa-like tumor cell (35,(42)(43)(44)(45). It was reported that miR-520h could target on IL-6R to inhibit cell growth (42).In the current study, an anti-proliferation property of miR-602 was revealed, we also identified that IL-6R was turned downed by miR-602 and induced by S-3′UTR.…”
Section: Discussionsupporting
confidence: 54%
“…IGF2, as a mitogen, is the first discovered parentally imprinted gene [ 24 ]. lncRNA IGF2-AS has been proved to play an important role in other diseases, including liver cancer [ 25 ], gastric cancer [ 26 ], and diabetic retinopathy [ 27 ], ect. However, there are still few reports on lncRNA IGF2-AS in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-520h, can exert both positive and negative effects on gene regulation in different cancers. Studies have reported that miR-520h induced pancreatic cancer cell death 44 , while promoted tumor growth and progression in hepatocellular carcinoma cell 45 , breast cancer 46 and epithelial ovarian cancer 47 . Our study revealed that miR-520h inhibited the translation of smad7, which further may lead to the suppression of the EMT process.…”
Section: Discussionmentioning
confidence: 99%